A cég, amelyik elébe ment a jövőnek - Az Országos Piackutató Intézet első évtizedeiről - szerk., Marketing & Menedzsment (Marketing & Menedzsment, 2017)
The company was established in 1967 just one year earlier than the so-called New Economic Mechanism was introduced in Hungary. The inventor and founder of the firm was Dr. László Szabó, who acted as the CEO for 25 years. The institute was launched to carry out the first market research tasks in Hungary. Its organisation and the methods used followed the West European trends. Besides undertaking market research for the manufacturer of consumer and industrial goods, in the eighties it started to do researches oversees to fulfil the requirements of the Hungarian economy. By the 90s, its information technology and the research methods became quite up-to-date. After the transition, it lost in importance and it was privatised by a communication agency under the name Marketing Centrum. To-day its role is rather marginal in market research. The founder of the Institute launched this Journal with the aim to inform potential customers about their work and methods they used and to make the Hungarian experts familiar with the those used in the foreign countries. Now celebrating the 50th jubilee of the journal, we can say that a new marketing generation was grown up on the pages of this journal. Since 1995, a non-profit institution the University of Pécs Faculty of Business and Economy took over first the half, later the full ownership of the journal, making their dream come true to have their own forum for scientific publications.